UTILIZING THE CROSS-GENDER FASHION PHENOMENON AS A CASE STUDY IN SOCIAL SCIENCES LEARNING FOR SOCIAL CHANGE MATERIALS FOR JUNIOR HIGH SCHOOL STUDENTS - Della Triya Junita Sari Sari (Jurnal Dialektika Pendidikan IPS, 2026)
This study aims to analyze the public's social construction of the cross-gender fashion phenomenon within the dance cover community in Surabaya and to describe its utilization as a case study in social studies learning on social change material. This research employs a qualitative approach with an instrumental case study design. Data were collected through observation, in-depth interviews with social studies teachers, members of the Xeon Explosion dance cover community, and the general public, as well as documentation. The results indicate that the public's social construction is ambivalent and contextual. Dance cover practitioners view it as a demand for professionalism and artistic expression, the general public shows passive tolerance by distinguishing between stage and everyday contexts, while social studies teachers see it as a symptom of social change that needs to be understood critically. This phenomenon reflects William F. Ogburn's theory of cultural lag. The utilization of this phenomenon in social studies learning is carried out through the Contextual Teaching and Learning (CTL) approach integrated with deep learning. The applied CTL syntax includes constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. This study concludes that the cross-gender fashion phenomenon has significant potential as a contextual learning resource capable of enhancing students' understanding of the concept of social change, critical thinking skills, as well as attitudes of tolerance and empathy.